Temperature effect of impulsive motion in an air floatation nozzle - Goh, Zhen Hwee, 1986- author; Kahar Osman; Fakulti Kejuruteraan Mekanikal (2014)
Thesis (Sarjana Kejuruteraan (Mekanikal)) - Universiti Teknologi Malaysia, 2014